Process-based information systems development: taking advantage of a component-based infrastructure - Pereira, José Luís (2017)
Background: Owing to the highly competitive business environment in which contemporary organizations have to operate, a quick and effective way of developing and maintaining information systems is of utmost importance to their success. Obviously, the computerized information systems that support the everyday operations and management of organizations play a critical role in their competitiveness. For that reason, nowadays, more than ever, information systems have to be quickly developed, rapidly reconfigured, and easily maintained. Objectives: We aim to define a technological infrastructure, accompanied by a set of methodological development requirements, which might help to fulfil those needs. Methods/Approach: In this work, we followed a Design Science Research (DSR) approach. Results: We propose a specific IT infrastructure, inspired by the concept of a business process and using the functionalities provided by collaborative and workflow technologies, which allows the development of distributed IT solutions, Process-Based Information Systems (PBIS), in a component-based fashion. In the context of PBIS, we also propose a set of development requirements. Conclusions: We claim that Process-Based Information Systems allow organizations to evolve quickly and smoothly in face of changing business requirements, facilitating the integration of existing and future IT artefacts, while simplifying the overall development and maintenance effort of information systems.